Sinergi Work-Life Balace dan Sistem Kompensasi dalam Meningkatkan Kepuasan Kerja: Perspektif Manajemen SDM - Khailanada Dien Arifin; Diah Ayu Anis Wulandari; Afrina Alya Faradilla; Rafika Meilia Sari (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study anims to analyze the role of human resource management (HRM) strategies in enhancing job satisfaction through the synergy between WLB and compensation systems. This study employs a qualitative approach using library research and a qualitative desriptive design. Data collection was conducted through the documentation method by reviewing various relevant and credible scientific literature, including national and international journal, reference books, and academic publications aligned with the research topic. The research model employed was conceptual analysis, while data analysis was conducted through the stages of data reduction, systematic data presentation, and interpretive conclusion-drawing. The research findings indicate that job satisfaction is signifixantly influenced by the integration of non-financial aspects specifically (WLB) and financial aspects specifically the compensation system. The implementation of effective HRM strategies, such as fair and trasparent compensation, work flexibility, and a supprotive organizational culture, canehance employee well-being, motivation, and loyalty. Furthermore, job satisfaction serves as a key variable that strengthens the relationship between HRM strategies and improved employee performance. Thus, the synergy between HRM strategies and improved employee performance. Thus, the synergy between WLB and compensation is a critical factor in creating a productive and sustainable.